2020
DOI: 10.4162/nrp.2020.14.6.553
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D regulation of adipogenesis and adipose tissue functions

Abstract: Vitamin D insufficiency is associated with obesity and its related metabolic diseases. Adipose tissues store and metabolize vitamin D and expression levels of vitamin D metabolizing enzymes are known to be altered in obesity. Sequestration of vitamin D in large amount of adipose tissues and low vitamin D metabolism may contribute to the vitamin D inadequacy in obesity. Vitamin D receptor is expressed in adipose tissues and vitamin D regulates multiple aspects of adipose biology including adipogenesis as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 82 publications
1
39
0
6
Order By: Relevance
“…Does obesity decrease vitamin D levels, does vitamin D deficiency promote obesity, or do they interact? On the one hand, researchers believe vitamin D bioavailability in obese individuals is decreased because of vitamin D deposition in body adipose tissue and altered expression levels of vitamin Dmetabolizing enzymes (2,7,17). Moreover, obese children are less likely to engage in outdoor activities, which results in reduced vitamin D synthesis (21).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Does obesity decrease vitamin D levels, does vitamin D deficiency promote obesity, or do they interact? On the one hand, researchers believe vitamin D bioavailability in obese individuals is decreased because of vitamin D deposition in body adipose tissue and altered expression levels of vitamin Dmetabolizing enzymes (2,7,17). Moreover, obese children are less likely to engage in outdoor activities, which results in reduced vitamin D synthesis (21).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, obese children are less likely to engage in outdoor activities, which results in reduced vitamin D synthesis (21). On the other hand, studies found that vitamin D regulated multiple aspects of adipose biology, such as adipogenesis and metabolic and endocrine function of adipose tissues (7). This may be the reason for obesity and metabolic diseases caused by vitamin D deficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, it is well-known that calcitriol can also induce non-genomic responses which involve the release of Ca 2+ into the cytosol [13,15,60]. One of the upregulated Ca 2+ -related proteins is RCAN1, whose expression is known to be induced via calmodulin-calcineurin-dependent Ca 2+ -signaling [61,62] and VitD3 has been shown to also involve calmodulin-dependent signaling [63,64]. These data further indicate that at least a part of the calcitriol-effects is mediated via Ca 2+ -signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Although VITD actions on adipose metabolism are controversial, there are several pieces of evidence that it regulates lipid synthesis, lipolysis and improves insulin signalling pathways. These results suggest that VITD may ameliorate adipose tissue dysfunctions, linking low VITD status to metabolic disease in obesity [ 12 ]. On the other hand, obesity per se seems to involve low circulating levels of VITD, due to low sun exposure, low physical activity, low intake of foods rich in VITD and volumetric dilution and sequestration in the adipose tissue.…”
Section: Introductionmentioning
confidence: 99%